Answer:
The first one:
−8x4−14x2−3
Step-by-step explanation:
(-4•2-1)(2•2+3)
-4•2 = -8
-8 - 1 = -9
(-9)(2•2+3)
2•2 = 4
4+3 = 7
(-9)(7) = -63
Now we find the one that equals -63:
-8•4-14•2-3
(-8•4)-14•2-3
-32-14•2-3
-32-(14•2)-3
-32-28-3
(-32-28)-3
-60-3
-60-3 = -63
BAM! THE ANSWER!
The solution for X= 0 and for y= 4x+11
Answer: 2w + 4 = 35
Step-by-step explanation:
Carl's two checked bags and his one backpack together weigh 35kg.
Carl's two checked bags have equal weight so both their weight can be denoted as 2w.
Equation is;
2w + 4 = 35
If you were to solve;
2w + 4 = 35
2w = 35 - 4
w = 31/2
w = 15.5kg
Answer:
![3x^{2} -3x+8-\frac{9}{x+1}](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20-3x%2B8-%5Cfrac%7B9%7D%7Bx%2B1%7D)
Step-by-step explanation:
Since we're dividing the polynomial by
, we'll be using -1 to start the division.
Before setting the division up, let's list the coefficients of
from descending powers and the constant.
The coefficient of
is 3
Since we don't see an
, the coefficient will be 0.
The coefficient of
is 5.
Lastly, the constant, which is the term without the
is -1.
Refer to the attached picture before continuing.
After referring to the picture, we now have the coefficients for the quotient.
The coefficient of
is 3.
The coefficient of
is -3.
The constant is 8.
Lastly, since the last number is not zero, it's the remainder just like regular division. This can be tricky to remember, but -9 is not the actual remainder.
The remainder is actually
.
Now putting all the pieces together, we get:
![3x^{2} -3x+8-\frac{9}{x+1}](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20-3x%2B8-%5Cfrac%7B9%7D%7Bx%2B1%7D)
I just added the two numbers and got the number 100.88